Pemberdayaan Petani Melalui Digitalisasi Agribisnis - M.ZAin, Majdah; Ibrahim, Helda; Musdalifah, Musdalifah; Asrib, Ahmad Rifqi (ADPERTISI, 2025)
This study aims to empower farmers in Takalar Regency through agribusiness digitalization. Despite having significant agrarian potential, farmers face challenges in marketing their products due to limited access to information and technology. Through a participatory approach, this activity involves outreach, training, and hands-on practice regarding the use of digital technology for online marketing. The results demonstrate an 80% increase in knowledge among participants, as well as the adoption of mobile applications and e-commerce platforms for product marketing. However, challenges such as limited internet access and digital literacy still need to be addressed. It is hoped that this program can strengthen food security and sustainably improve farmers' welfare.